MANAGEMENT TRANSFORMATION IN THE HOSPITALITY INDUSTRY IN YOGYAKARTA (2014-2024) - Ristanti Ristanti; Sonny Heru Priyanto; Dwiyono Rudi Susanto; Ratih Titik Haryati; Herra Herra; Bawa Mulyono Hadi (PT. Jurnal Center Indonesia Publisher, 2025)
In today's digital era, revitalizing the hospitality industry through technological innovation is crucial for enhancing competitiveness and improving customer experience. By gaining a deeper understanding of customer needs and developing service innovations, hotels can deliver more personalized and satisfying experiences. This shift in vision toward better customer service underscores the need for continued research on the paradigm shift within the hospitality sector. This study aims to observe and explore changes in the hospitality industry, with the goal of identifying paradigm evolutions and their contributions to service efficiency and quality. The research is expected to offer new insights into the dimensions of customer experience and internal operations that require rethinking, while also identifying cohesive strategies to integrate digital and physical elements. Furthermore, it analyzes the impact of hotel development control policies, management strategies, and technological innovations, thereby contributing both theoretically and practically to the development of the hospitality industry in Yogyakarta in response to the challenges of digital transformation.